Pertanggungjawaban Pidana terhadap Anak Ditinjau dari Hukum Pidana Islam dan Undang-undang Nomor 11 Tahun 2012 Tentang Sistem Peradilan Pidana Anak - Nabilla, Alifia Desya; Azizah, Noor; Ramadani, Ramadani (AHKAM, 2023)
A child who commits a crime is a child with problems, who lives in an unhealthy family or social environment. Then comes the behavior of children who are not in accordance with the norms in society. As a result, the child must be held accountable for his actions. However, the ability of children to be responsible for their actions varies according to the ability to think according to the time they go through. The purpose of this study is to determine criminal responsibility for children in terms of Islamic criminal law and Law no. 11 of 2012 concerning the Juvenile Criminal Justice System and to find out the differences and similarities and which laws are relevant between the two laws. The type of research used is normative juridical law research, using a descriptive and comparative approach and the sources of legal materials used in this research are primary and secondary sources of legal materials. The results of this study show that between Islamic criminal law and Law Number 11 of 2012 concerning the juvenile justice system, there are differences and similarities in terms of criminal responsibility for children, where the differences are in the legal basis, the age limit for children to sanctions and similarities in both laws. both of them put forward the best interests of the child through diversion in the form of a restorative justice approach, both determine the factors of reason and will as the main conditions for being responsible and equally provide teaching and direction to children who commit crimes.